Drug inhibition and substrate transport mechanisms of human VMAT2 - Feiwen Wei; Huihui Liu; Wei Zhang; Jufang Wang; Yanqing Zhang (Nature Communications)
Abstract Vesicular monoamine transporter 2 (VMAT2) is crucial for packaging monoamine neurotransmitters into synaptic vesicles, with their dysregulation linked to schizophrenia, mood disorders, and Parkinson’s disease. Tetrabenazine (TBZ) and valbenazine (VBZ), both FDA-approved VMAT2 inhibitors, are employed to treat chorea and tardive dyskinesia (TD). Our study presents the structures of VMAT2 bound to substrates serotonin (5-HT) and dopamine (DA), as well as the inhibitors TBZ and VBZ. Utilizing cryo-electron microscopy (cryo-EM), mutagenesis functional assays, and molecular dynamics (MD) simulations, we elucidate the mechanisms of substrate transport and drug inhibition. Our MD simulations indicate potential binding poses of substrate (5-HT) in both cytosol-facing and lumen-facing states, emphasizing the significance of protonation of key acidic residues for substrate release. We demonstrate that TBZ locks VMAT2 in a lumen-facing occluded state, while VBZ stabilizes it in a lumen-facing conformation. These insights enhance our understanding of VMAT2 function and provide valuable insights for the development of novel therapeutic strategies for psychiatric disorders.